Contemporary Environmental Standards in Islamic Education Books for the Secondary Stage in Jordan: Analytical Study - Albustanji, Iyad Yousef (Journal of Educational and Psychological Sciences, 2020)
This study aimed to identify the extent to which the Islamic education books of the secondary stage in Jordan are of interest to contemporary environmental standards. Study community, the Islamic Education Books for the secondary stage issued by the Ministry of Education for the academic year 2019/2020. Which is taught at all the schools of the Hashemite Kingdom of Jordan. To achieve the objectives of the study, the researcher built a list of contemporary environmental standards then developed into a tool to analyze the books mentioned. The method of the study was based on five axes, which included fifteen contemporary environmental criteria. (Science and technology, cooperation, ethics, values ​​and behavior, culture and media, legislation and oversight). The descriptive method was used based on the method of content analysis. The stability coefficient was extracted using the Holsti equation for stability. The coefficient of stability over time (7.89%), persons (8.86%), this coefficient is acceptable for study purposes, and the results of the study revealed the low availability of contemporary environmental standards in those books, and Including the environmental dimension in Islamic education books for high school in Jordan by entering environmental information and concepts or linking the content to appropriate environmental issue. In light of the results of the study, the researcher recommended work on the integration of Islamic education courses in the secondary stage, the environmental axes are introduced gradually according to a balanced hierarchical organization, by introducing environmental information and concepts, or linking the content to appropriate environmental issues